Neutron and X-ray powder diffraction study of skutterudite thermoelectrics. Issue 1 (17th February 2016) - Wang, H.; Kirkham, M. J.; Watkins, T. R.; Payzant, E. A.; Salvador, J. R.; Thompson, A. J.; Sharp, J.; Brown, D.; Miller, D.
Abstract : N- and p-type filled-skutterudite materials prepared for thermoelectric power generation modules were analyzed by neutron diffraction at the POWGEN beam line of the Spallation Neutron Source (SNS) and X-ray diffraction (XRD). The skutterudite powders were processed by melt spinning, followed by ball milling and annealing. The n-type material consists of Ba–Yb–Co–Sb and the p-type material consists of Di–Fe–Ni–Sb or Di–Fe–Co–Sb (Di = didymium, an alloy of Pr and Nd). Powders for prototype module fabrication from General Motors and Marlow Industries were analyzed in this study. XRD and neutron diffraction studies confirm that both the n- and p-type materials have cubic symmetry. Structural Rietveld refinements determined the lattice parameters and atomic parameters of the framework and filler atoms. The cage filling fraction was found to depend linearly on the lattice parameter, which in turn depends on the average framework atom size. This knowledge may allow the filling fraction of these skutterudite materials to be purposefully adjusted, thereby tuning the thermoelectric properties.